European Philosophers Radim Palouš and Jozef Piaček on Phenomenological Themes of Education, Syncriticism and Philosophy of Concordance - Peter Rusnák; Marcel Martinkovič (Nicolaus Copernicus University in Toruń, 2023)
In the present article, the possibilities of teaching the philosophy of syncriticism and life of concordance as conditio humana and mediation of philosophical thinking to youth (students) and teachers in the era of ignorance (Konrad Paul Liessmann) are discussed. Using the philosophical concept of syncriticism, the author attempts to open and defend the otherness of philosophy in the system of education, justify its enriching and provocative dimension, its free-teaching time (Jan Patočka), life practice in building relationships and the authentic life of our everyday existence (Radim Palouš). In the philosophy of syncriticism and competence of concordance (Jozef Piaček) and in indifference to the future, we see the meaningfulness of philosophical education and find its new possibilities and challenges concerning homo educandus.